Analysis of Business Process Re-Engineering in the Implementation of Robotic Sorting Machines in the Middle Mile Process at PT Pos Indonesia (Persero) - Imam Pujono; Tukhas Shilul Imaroh (PT FORMOSA CENDEKIA GLOBAL, 2024)
PT Pos Indonesia faces challenges in improving courier service business processes due to business change trends. This study aims to identify and analyze inefficiencies in the middle mile supply chain business process of PT Pos Indonesia Processing Centre Surabaya and determine the number of robotic mega bots needed to improve efficiency. The research method uses quantitative information, observations, interviews, computer simulations, Value Stream Mapping process flow charts, and Business Process Reengineering concepts. The results showed that the use of mega bot robots had a positive and significant impact on the company's reputation, and the sorting process carried out using robotic mega bots was appropriate because it had a significant impact on the effectiveness and efficiency of business process improvements at PT Pos Indonesia (Persero).